The Dynamics of Party Cartels: Obstacles to Reforms and Reinforcers of Political Corruption in Indonesia - Yeni Sri Lestari; Fadli Afriandi; Ligar Abdillah (Universitas Muhammadiyah Yogyakarta, 2025)
Political reform in Indonesia has produced a paradox within the country’s political dynamics. While the reforms were intended to strengthen democracy, they have instead contributed to its weakening and facilitated the rise of political cartel practices. These practices are marked by the consolidation of opposition parties, the erosion of party ideologies, and the prioritization of ruling elite interests through unfettered access to state resources. The decline of ideological commitment among political parties has led to the emergence of cartelized party coalitions, which in turn promote political corruption, weaken mechanisms of checks and balances, and undermine the overall quality of democracy. This article employs a qualitative research methodology, focusing on literature reviews of scholarly books and academic articles related to political corruption and cartel politics in Indonesia. The findings indicate that the entrenchment of political cartels is a major driver behind the increasing incidence of political corruption in Indonesia. The dismantling of political cartel structures is therefore essential to curbing corruption. The shift away from ideological politics towards opportunistic alliances aimed at extracting benefits from state resources has exacerbated corrupt practices. Reforming Indonesia's party system is thus imperative to breaking the cycle of political cartelization and reducing the pervasive corruption among political elites. The novelty of this study lies in its in-depth analysis of how political parties, once vehicles of democratic expression, have transformed into instruments of collusion and corruption. This transformation has led to new configurations of power relations and the unequal distribution of state resources. The implications of this study underscore the urgent need for party system reform and the reinforcement of democratic institutions as essential strategies for effectively combating political corruption in Indonesia moving forward.